Edukasi Dampak Penggunaan Gadget bagi Kesehatan Anak di LKSA Widhya Asih Badung - I Wayan Widi Karsana; Rai Riska Resty Wasita; Agus Donny Susanto; Nyoman Ngurah Adi Sanjaya; Bambang Hadi Kartiko; I Gusti Ngurah Manik Nugraha; Ni Wayan Deswiniyanti; Wayan Nurata; Putu Okta Wijayanti; Made Dewi Sariyani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
In the current digital era, gadget use has become an inseparable part of everyday life, including among children. However, excessive use of gadgets can have a significant impact on children's health. This service activity aims to provide education regarding the negative impact of gadget use on children's health. Excessive use of gadgets can cause mental health and physical health problems, including disturbances in body posture and vision problems due to exposure to blue light which can affect their growth and development. Results The pre-test carried out before the educational activity resulted in only 27.5% understanding the impact of using gadgets on health, while the test carried out after the education resulted in 77.5% understanding the impact of gadgets on health. This shows an increase in understanding of 50% after it was carried out. education regarding the impact of gadget use on children's health.